De sermone (1733) - Hassel, Henrik; Ljung, Ericus Petri; Kämpe, Johan (kirjapaino, Turku, 1729-1753); Turun Akatemia; Royal Academy of Turku; Regia Academia Aboensis; Kungliga akademin i Åbo; Gilberg, Andreas; Krook, Jacobus Benedicti (Aboae : excud. Joh. Kiämpe R. Ac. typ., [1733], 1733)
Variantti A.
Keywords: kielitiede